FORMS AND HISTORICAL ROOTS OF THE MAKHALLA - raupov, soyib (Центр Научных Публикаций (buxdu.uz), 2021)
In the following article, the concept of makhalla, its essence, function, the responsibilities and the duties of the alderman of the makhalla are studied from the viewpoint of historical trends.